Enhancing Islamic Education Through PAIS Work Programs: A Case Study in Sleman District's Ministry of Religious Affairs - Arlin Prima Sari (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study aims to explore the effectiveness of the Islamic Education Program Work (PAIS) in enhancing the professionalism of Islamic Education teachers (PAI) and its impact on the development of Islamic education within Sleman District's Ministry of Religious Affairs. By identifying strengths, limitations, and areas for improvement in these programs, the research seeks to provide valuable insights and recommendations that can guide future strategies and initiatives in the field of Islamic education. Design/methods – Adopting a qualitative research methodology with a descriptive case study design, this research was set in the Ministry of Religious Affairs in Sleman District. The study employed a variety of data collection methods including observation, semi-structured interviews, and literature review. The primary participant was the head of the PAIS work unit, Mr. Sangaji, S.H.I. Data analysis involved data reduction, data display, and data verification phases to ensure the validity and accuracy of the findings. Findings – The research revealed that PAIS work programs significantly contribute to the professional development of PAI teachers and the overall quality of Islamic education. These programs support strategic planning, stakeholder engagement, and the incorporation of technology in education, thus creating a dynamic and effective educational environment. However, challenges such as limited funding, competency and commitment standardization, and optimal parental support were identified. Research implications/limitations – The implications of this research extend beyond Sleman District, providing insights into the potential of targeted educational programs to enhance Islamic education quality. However, the study is limited by its focus on a single institution and the specific cultural and administrative context of Indonesia, which may influence the generalizability of the findings. Practical implications – This study underscores the importance of strategic planning, stakeholder engagement, and technological integration in Islamic education. Addressing the identified challenges can aid in overcoming barriers to effective education and contribute to fostering a knowledgeable and ethical society. Originality/value – This research offers a unique examination of the impact of digital transformation within the context of Islamic education in Indonesia, particularly through the lens of PAIS work programs in the Ministry of Religious Affairs. It contributes to the broader understanding of digital transformation in education, highlighting the intersection of technology, education, and culture in a religious educational setting.